FAKTOR PENYEBAB KERENGGANGAN HUBUNGAN ORANG TUA DAN ANAK DI ERA DIGITAL - Nessa Suriani; Rara Dipa Aresta; Siti Nadhira; Netti Lubis; Melsa Susanti; Nurul Inayah Hutasuhut (JURNAL ILMIAH NUSANTARA, 2026)
Digital technology development has changed family life, especially communication patterns between parents and children. The increasing use of gadgets provides both positive and negative impacts on family relationships. This study aims to identify the factors causing strained relationships between parents and children in the digital era. The research used a qualitative method with questionnaires distributed to 13 parent respondents. The results show that most respondents use gadgets or social media every day. In addition, most respondents believe that gadget use during family gatherings reduces communication between parents and children. Meanwhile, work-related busyness is not considered the main cause of strained family relationships. Therefore, excessive gadget use during family time is the most dominant factor causing strained relationships between parents and children.